Conflict of interest dalam Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Tentang Pengujian Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum - Mulazi Ibna Fikra (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
The Constitutional Court Decision Number 90/PUU-XXI/2023 decided that the Chief Justice of the Constitutional Court Anwar Usman was declared to have violated the code of ethics of the Sapta Karsa Hutama principle by the Honorary Panel of the Constitutional Court regarding the age limit of presidential and vice presidential candidates. Anwar Usman was proven to have committed serious violations of the Code of Ethics and Behavior of Constitutional Judges as stated in Sapta Karsa Hutama, the Principles of Impartiality, the Principles of Integrity, the Principles of Proficiency and Equality, the Principles of Independence, and the Principles of Decency and Decency. This research is normative juridical with a statutory approach. The results of this study indicate that in the Constitutional Court Decision number 90/PUU-XXI/2023 concerning the Examination of Law Number 7 of 2017 concerning General Elections against the 1945 Constitution of the Republic of Indonesia, it is true that there is a conflict of interest and violates the principle of Impartiality. This is evidenced by mentioning the name Gibran Rakabuming Raka who is the nephew of Judge Anwar Usman's wife so that the testing of abstract norms becomes measurable.